The chaperonin CCT8 controls proteostasis essential for T cell maturation, selection, and function - Bergithe E. Oftedal; Stefano Maio; Adam E. Handel; Madeleine P. J. White; Duncan Howie; Simon Davis; Nicolas Prevot; Ioanna A. Rota; Mary E. Deadman; Benedikt M. Kessler; Roman Fischer; Nikolaus S. Trede; et al. (Communications Biology, 2021)
Oftedal et al. generate mice lacking the chaperonin subunit CCT8 in T cells. They find that loss of CCT8 leads to reduced formation of nuclear actin filaments, changes in proteostasis, defective Th2 cell polarization and T cell metabolism and a failed antigenic response to intestinal helminths.